The Impact of the Snakes and Ladders Game on Students' Vocabulary - Sugiyati, Sugiyati; Sujarwati, Iis (International Journal of Innovation and Education Research, 2025)
Learning vocabulary is an essential part of language development, as it helps students improve their communication and comprehension skills. Teachers play a key role in this process by using effective methods to teach new words in ways that are engaging and meaningful. Games such as Snakes and Ladders  is one of  tools  for teaching vocabulary, creating enjoyable learning experiences that enhance students' understanding and retention of new words. The study aims to explore whether this game-based learning approach can help students learn and remember new vocabulary more effectively. The research seeks to provide valuable insights into the role of interactive games in making vocabulary learning more enjoyable and impactful. This study uses an experimental design to investigate the effect of the Snakes and Ladders game on students’ vocabulary mastery. A sample  is divided into an experimental group, using the game, and a control group, following traditional methods. Both groups complete a pre-test and post-test consisting of 25 multiple-choice questions based on the Merdeka Curriculum. The data is analyzed using descriptive statistics and a T-test to compare the scores, determining whether the game significantly improves vocabulary mastery. The results show a significant improvement in students' vocabulary mastery after using this game. The results revealed an average increase. Statistical analysis using the paired sample T-test confirmed that this improvement was highly significant . These findings highlight the effectiveness of this game as an engaging tool for enhancing students' vocabulary skill. This study demonstrates that this game significantly enhances students' vocabulary mastery. Keywords: The Effect, Snack and Ladder Game, Vocabulary Mastery